PD-1 inhibitor combined with chemotherapy for first-line treatment of esophageal squamous cell carcinoma patients with distant metastasis: a real-world retrospective study - Gao, Loulu; Tang, Lin; Peng, Jieqiong; Hu, Zixuan; Yang, Jing; Liu, Bo (Frontiers in Immunology, 2024)
The aim of this study was to evaluate whether the efficacy and safety of PD-1 inhibitors combined with chemotherapy in the treatment of patients with esophageal squamous cell carcinoma (ESCC) with distant metastasis in the real world are as effective and safe as in clinical trials.From July 2019 to July 2023, a total of 422 patients with distant metastasis of ESCC were included and divided into the PD-1 inhibitor combined chemotherapy group (PC group) and the chemotherapy alone group (C group) according to the treatment regimen.There were 278 patients in the PC group and 144 patients in the C group. The primary endpoint of this study was progression-free survival (PFS), while secondary endpoints included objective response rate (ORR), disease control rate (DCR), overall survival (OS), and safety.The objective response rate (ORR) and disease control rate (DCR) of the PC group were 44.60% (124/278) and 91.00% (253/278), respectively, which were 18.9% and 3.5% higher than those of the C group. The median PFS and median OS of the PC group were significantly better than those of the C group (median PFS: 6.5 vs. 5.5 months, P ＜ 0.001; median OS: 16.6 vs. 13.9 months, P = 0.002). Further univariate and multivariate Cox analysis showed that the Eastern Cooperative Oncology Group performance status (ECOG PS) score and the number of metastatic sites were potential predictors of PFS in PC patients. The combination of PD-1 inhibitors with cisplatin and paclitaxel (TP) was more beneficial for patients with PFS compared to the combination of cisplatin and fluorouracil (PF). Furthermore, the presence of bone metastasis, body mass index (BMI), and lymphocyte-to-monocyte ratio (LWR) before treatment may be potential predictive factors for patient OS. The adverse reactions that occurred in the PC group can be tolerated or alleviated after both prevention and active treatment.The combination of PD-1 inhibitors and chemotherapy as first-line treatment for ESCC patients with distant metastasis still has good efficacy and safety compared to clinical trials in the real world.